The Role of Emerging IT Technologies in Agriculture - Subhadra, Kannepalli (International Journal of Computer Sciences and Engineering, 2020)
Agriculture sector in India is moving back day by day which affects the production capacity of ecosystem. Agriculture has usually been treated as an instinctive space with insight passed down from one generation to another. But today’s problems like the climate change, reduction of feasible farmland, reduction of water resources, and the loss of productivity due to the occurrence of extreme weather events are more complex and vital in the present nature. The United Nations estimates that the global population will reach 9.8 billion by 2050 that is a 2.2 billion increase from now [1]. This means that there is a need to improve our crop production significantly to supply to the rising number of people. One of the important things that are associated with present agriculture is the capability to forecast the events that will produce a desired outcome. Farmers need proper information throughout the entire farming cycle to achieve the goals. The required information is sprinkled in various places which includes actual information such as market prices and current production level along with the existing primary crop knowledge. The world around agriculture requires automation by replacing manual procedures with the expansion of technology, because it is energy efficient and takes minimal man power. Some farmers simply cannot increase their land to cultivate more crops, in that situation there is a need for technology to make better use of the available space in an efficient manner. This situation leads for technological innovation, to face the challenges like extreme weather conditions, rising climate change, and farming’s environmental impact. To meet these increasing needs, agriculture has to revolve to new technology. Now a day’s there is rapid enhancement in technologies,